Heart Failure With Targeted Cancer Therapies: Mechanisms and Cardioprotection. Issue 10 (14th May 2021) - Hahn, Virginia S.; Zhang, Kathleen W.; Sun, Lova; Narayan, Vivek; Lenihan, Daniel J.; Ky, Bonnie
Abstract : Oncology has seen growing use of newly developed targeted therapies. Although this has resulted in dramatic improvements in progression-free and overall survival, challenges in the management of toxicities related to longer-term treatment of these therapies have also become evident. Although a targeted approach often exploits the differences between cancer cells and noncancer cells, overlap in signaling pathways necessary for the maintenance of function and survival in multiple cell types has resulted in systemic toxicities. In particular, cardiovascular toxicities are of important concern. In this review, we highlight several targeted therapies commonly used across a variety of cancer types, including HER2 (human epidermal growth factor receptor 2)+ targeted therapies, tyrosine kinase inhibitors, immune checkpoint inhibitors, proteasome inhibitors, androgen deprivation therapies, and MEK (mitogen-activated protein kinase kinase)/BRAF (v-raf murine sarcoma viral oncogene homolog B) inhibitors. We present the oncological indications, heart failure incidence, hypothesized mechanisms of cardiotoxicity, and potential mechanistic rationale for specific cardioprotective strategies.